The magic finger - Dahl, Roald; Blake, Quentin (London : Puffin Books, 2014)
Angered by a neighboring family's sport hunting, an eight-year-old girl turns her magic finger on them.
3.5
3-6.
3-6
Keywords: Hunting -- Juvenile fiction; Magic -- Juvenile fiction; Hunting -- Fiction; Magic -- Fiction; Hunting -- Fiction; Magic -- Fiction; Fantastic fiction; Fantastic fiction; Fantastic fiction